Cost Utility of Bronchial Thermoplasty for Severe Asthma: Implications for Future Cost-Effectiveness Analyses Based on Phenotypic Heterogeneity - Keim-Malpass J; Malpass HC (Dove Medical Press, 2022)
Jessica Keim-Malpass,1- 3 H Charles Malpass4 1University of Virginia School of Nursing, Charlottesville, VA, USA; 2Department of Pediatrics, University of Virginia School of Medicine, Charlottesville, VA, USA; 3University of Virginia Center for Advanced Medical Analytics, Charlottesville, VA, USA; 4Department of Pulmonary and Critical Care Medicine, University of Virginia School of Medicine, Charlottesville, VA, USACorrespondence: Jessica Keim-Malpass, University of Virginia School of Nursing, PO Box 800782, Charlottesville, VA, 22908, USA, Email Jlk2t@virginia.eduBackground: Asthma is a disease with tremendous phenotypic heterogeneity, and the patients who are most severely impacted by the disease are high utilizers of the United States healthcare system. In the past decade, there has been many advances in asthma therapy for those with severe disease, including the use of a procedure called bronchial thermoplasty (BT) and the use of biologic therapy for certain phenotypes, but questions remain regarding the long-term durability and cost effectiveness of these therapies. The purpose of this analysis was (1) to assess the cost utility of BT relative to usual care (base case) and (2) to assess the cost utility of BT relative to usual care plus biologic therapy (omalizumab) (scenario analysis) based on updated 10-year clinical trial outcomes.Methods: A Markov cohort model was developed and used to estimate the cost utility of BT to estimate the costs and quality-of-life impact of BT versus the comparisons over a 10-year time frame using a limited societal perspective, which included both direct health utilization costs and indirect costs associated with missed days of work, among those with severe persistent asthma.Results: In the base case and the scenario analysis, BT was the dominant treatment strategy compared to usual care alone and usual care plus biologic therapy. The net monetary benefit for BT was $483,555.49 over a 10-year time horizon.Conclusion: Cost-utility models are central to policy decisions dictating coverage, and can be extended to inform the patient and provider, during clinical decision-making, of the relative trade-offs of therapy, assessing long-term clinical and cost outcomes. Phenotypic classification of severe asthma is central to patient management and should also be integrated into economic analysis frameworks, particularly as new biologic agents are developed that are specific to a phenotype. Despite a larger upfront cost of BT therapy, there is a durable clinical and economic benefit over time for those with severe asthma.Keywords: asthma, bronchial thermoplasty, cost-effectiveness analysis, economic evaluation, heterogeneity, cost-utility analysis, phenotype